Liturgy and Morality. Constitution on the Sacred Liturgy Sacrosanctum Concilium in the Context of Moral Theology - Bogusław Mielec (Ruch Biblijny i Liturgiczny, 2013)
The fiftieth anniversary of the promulgation of the Constitution on the Sacred Liturgy of Vaticanum II encourages attempts of its interpretation in the context of moral theology. It leads to the conclusion that there is a co-relation between liturgy and morality in the history of salvation. The Revelation of the Old Testament reveals the conjunction between worship and morality. Attempts to separate the two in the history of the Chosen People raise objections of prophets. Their criticism, however, comes together with the announcement of the future in which God will reveal the divisions between worship and morality. The New Testament shows the fulfilment of this promise in Jesus Christ. His salvific work establishes the Christian liturgy, in which man participates as a physical, as well as a spiritual being. The salvation, made present in the liturgy of the Church, is a relation, the co-operation of God and man, grace and freedom. Sacrosantum Concilium presents this revealed truth, emphasising the objective and subjective dimensions of liturgy as the work of Christ, in which a Christian participates actively, freely and consciously (participatio actuosa). The participation is mostly spiritual, therefore moral at the same time. Only than can the external elements of liturgy take place, including its detailed forms, gestures, attitudes and behaviours of the sacred liturgy participants. It means that the liturgical participatio actuosa requires moral works through imitation of Christ leading to conversion. That is when “faith works through love” (cf. Gal 5 : 6). It leads us to the notion of sacrifice, which, as far as man is concerned, requires a total change. Sinful man presented with the love of the Triune God may respond to it with his own, gradually maturing love. The process constitutes the drama of God and man, which is the tension between grace and freedom, which is then represented by the co-relation between liturgy and morality. What is more, this particular co-relation makes an authentic experience of liturgy possible, protecting it from being reduced to sheer moralism and ritualism.